Optimalisasi BMD Pemprov Jabar melalui KSP dengan Badan Usaha Dibandingkan dengan Dikelola melalui Pola BLUD (Studi Kasus pada GOR Saparua) - Zalfa Rofia Maulidina; Etti Ernita Sembiring (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
This study aims to find the most appropriate form of utilization operator for GOR Saparua. In order to achieve a balance of social and economic functions, an ideal and effective form of management is needed for Saparua. According to Permendagri No.19 of 2016, one form of utilization of BMD is the coorporation with Business Agencies, where Saparua will be seen as a source of income. Saparua also provide services to the community so that its utilization will be compared with the form of management by BLUD which is social but also implements business practices. This study uses a credibility test with triangulation techniques. The research method used is a qualitative method with a descriptive approach. The results of this study indicate that the projected income and operating costs are in deficit, whether managed by the Business Agencies or BLUD. If look by conditions and facilities, it would be more suitable to be managed by BLUD because to cover the deficit in operational costs, it can only be helped from the Government budget).